Levi's basic anxiety, conflict and the search for glory in Zadie Smith's On Beauty - Shokri, Shima; Bahar, Ida Baizura; Noor, Rohimmi (Universiti Putra Malaysia Press, 2016)
Literary scholars of Zadie Smith's novel 'On Beauty' (2005) have examined Levi, the youngest male character of the novel, based on his environment, a multicultural society, and have viewed him as a representation of a multicultural family. However, this paper analyses Smith's portrayal of Levi as an ordinary child who grew up in unfavourable conditions. For this purpose, Levi's character is analysed as a representation of neuroticism and his basic anxiety, need for detachment, self-idealisation and search for glory are explored using a conceptual framework based on Karen Horney's psychoanalytic social theory. Through textual analysis, this study attempts to explore the root of psychological anxiety in Levi to discover the role of basic conflict in his behavioural and emotional responses, and to examine how Levi copes with his anxiety through self-idealisation. The outcomes indicate that, as the root of his basic anxiety, Levi's relationship with his father, transforms him into a detached person attempting to prove himself. This paper clarifies that Levi's conflict is rooted in the manner of his nurturing, with some impact from other factors such as society, culture and racial issues. In order to justify that the difficulties faced by multicultural families are not only related to their cultural and racial identity, future research could apply Horney's theory for literary works categorised under multiculturalism and immigration.